Essentials of private warehousing - Ang, Chew Her (2008)
This project works on the essentials of establishing a bonded warehouse through evaluating the various existing industrial sites, warehousing space requirement analysis, designing of facility/ product layout and the storage concept analysis. Therefore, the selected warehouse facility will have all the necessary features to achieve the optimal operating efficiency of a self-own bonded warehouse and improve the profitability of GLPL in the long run.